Differences and allometric relationships among assimilative branch traits of four shrubs in Central Asia - Meng, Huan-Huan; Yin, Ben-Feng; Li, Yong-Gang; Zhou, Xiao-Bing; Zhang, Yuan-Ming; Tao, Ye; Zhou, Duo-Qi (Frontiers in Plant Science, 2022)
Shrubs play a major role in maintaining ecosystem stability in the arid deserts of Central Asia. In this study, four dominant shrubs with assimilative branches, namely Haloxylon ammodendron, Haloxylon persicum, Caligonum mongolicm, and Ephedra przewalskii, were selected as the research objects, and the dry mass, total length, node number, and basal diameter of their assimilative branches and the average length of the first three nodes were carefully measured. Results showed that the variations in five assimilative branch traits were mainly caused by interspecific differences, and each trait presented a significant difference among the four shrubs, and the regularity was also different, reflecting the interspecific variations. The scaling exponents of the allometric relationship between four traits and the dry mass of assimilative branches of H. persicum were greater or significantly greater than those of H. ammodendron, but there were no significant differences among other traits. The scaling exponents of the allometric relationship between the number of nodes and basal diameter, dry weight, and length of assimilative branches of H. ammodendron and H. persicum had small or significantly smaller values than those of C. mongolicm and E. przewalskii. Compared to the assimilative branches of the other three shrubs, the scaling exponents of the relationships between the number of nodes and basal diameter, the total length and dry mass, and the number of nodes and dry weight had the largest values in C. mongolicm, whereas the scaling exponents of relationships between basal diameter, dry mass, and total length had the smallest values. The scaling exponents of the relationships between the basal diameter, dry mass, and total length of E. przewalskii, however, were greater than those of the other three shrubs. Therefore, although different species have adapted to drought and high temperatures by convergence, there was great variability in morphological characteristics of assimilative branches, as well as in the scaling exponents of relationships among traits. The results of this study will provide valuable insights into the ecological functions of assimilative branches and survival strategies of these shrubs to cope with aridity and drought in desert environments.